(untitled) (Al-Qamar, 2020)
The family organizes the foundation of society and its strength or weakness is based on the strength or weakness of its society. If the family system is weak then nothing can replace it. The signed article is an excuse for a comparative study of Islamic and Western conceptions of the family. In Islam, the concept of family, its organization and importance are discussed and compared with the diverse family framework of the West. The family is a part of the Islamic social system. The society that Islam seeks to establish is not a sensitive, sexist society. It establishes an ideological society with a high level of moral awareness. Islam has given the highest moral values ​​to its caste and all the activities of life. This research article shows that despite its present greatness, the whole West is heading towards a catastrophic end. The breakdown of Western families continues at an alarming rate. Rising divorce rates, unmarried and same-sex relationships, physical and sexually transmitted diseases show that the West is at the top of the world. Islam, on the other hand, protects the race and provides a very smooth family system, such a system in which every family member is close to each other and treated with love and respect. The position of woman in Islamic family system is no less than that of any goddess. Sometimes she is worshiped in the form of mother, sometimes in the form of sister, daughter and wife, her every word is considered as the last word and her every wish is fulfilled.